(untitled) (Olhar de Professor, 2011)
This research integrated qualitative methodologies and techniques in order to approximate the reality studied. As a descriptive and exploratory case study, the study had as its theoretical basis contemporary studies on qualitative research methodology (BOGDAN; BIKLEN, 1994; SANCHEZ GAMBOA, 2003; FLICK, 2002, among others). The selected techniques (questionnaire, interview, focus group, video recording and diagram) were used to collect data about consumer technologies with students from a public elementary school in Sao Paulo. These techniques allowed the identification of important data on the use of technology by students in three areas: consumer technology for personal use, use of technology in school and knowledge about e-waste discard. The set of quantitative and qualitative data confirmed the use of digital technologies characterized by access to social media. The study also revealed the challenges related to the infrastructure necessary for the integration of technology in school activities and about ecological awareness for the disposal of electronic waste. The integration of quantitative and qualitative techniques contributed to a better understanding of the phenomenon studied. The methodological approach of the data supported by relevant studies favored the representations of the analytical process, allowing for a comprehensive analysis. The study also demonstrated that the complexity in finding quality in research depends more on the logic of connections than on the technical choices, confirming the value added to the crossing of theoretical and methodological perspectives of qualitative research.